Estudo do uso do extrato de Citrus aurantium subsp. amara (L.) (laranja amarga) na redução de peso em modelos roedores - Xavier, Kaiane Muriel da Silveira de Lima (2020)
Obesity, or overweight, in the modern world, is one of the biggest public health problems. The pace of everyday life leads people to eat wrong, opting for industrialized foods and fast foods. Excessive fat accumulation is not only an aesthetic problem, obesity leads to comorbidities such as: diabetes, high blood pressure, cardiovascular diseases, and others. Medicinal plants are widely used in both folk and traditional medicine. It is estimated that about 25% of the medicines used in the medical clinic come from plants. The substances used to treat obesity have an appetite-inhibiting, metabolism-accelerating, diuretic and / or lipolytic action. Citrus, in general, is widely used as dietary supplement, mainly the extract of Citrus aurantium subsp. amara (L.) (bitter orange), as a slimming and metabolism accelerator. The main active constituent is synephrine, comprising about 90% of the total protoalkaloids. Synephrine is also responsible for the slimming effect, because through its action on β-3 adrenergic receptors it increases metabolism and lipolysis, thus culminating in weight loss. Bitter orange extract is able to act on the individual's metabolism, helping to treat obesity effectively, without presenting toxicity when used in isolation. This project aims to evaluate the action of Citrus aurantium subsp. amara (L.) in weight loss in obese rats; point out its side effects on the nervous and cardiac systems and clarify what is its action in relation to biochemical changes. To make this possible, 5 groups of rodents were used, divided into: negative control, positive control and groups 1, 2 and 3, which received different doses of C. aurantium. During the entire treatment with the bitter orange extract, the rodents were kept on a high-calorie diet so that the action of the medication could be tested in isolation. Throughout the research the animals were evaluated for behavior and anxiety. At the end of the treatment, the rats were euthanized and evaluated for action and side effects by means of biochemical and hematological tests. After analyzing the results, it was noted that in all groups it was not possible to observe weight reduction and / or inhibition of animals appetite. It is suggested that further research with greater durability of time and that include a balanced diet be carried out so that the action of bitter orange in the body can be fully assessed.